ANALISIS FAKTOR YANG MEMPENGARUHI PENINGKATAN URBANISASI DI KOTA JAKARTA DAN SURABAYA PADA TAHUN 2020-2021: 1. Untuk Mengetahui alasan mendasar Urbanisasi di Kota Jakarta dan Surabaya 2. Untuk mengetahui dampak peningkatan Urbanisasi di Kota Jakarta dan Surabaya 3. Untuk mengetahui faktor pendukung dan Penarik dari Urbanisasi di Kota Jakarta dan Kota Surabaya (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
In this study, the core problem is why the population outside the cities of Jakarta and Surabaya enters the two cities, causing an increase in the number of residents beyond their capacity. With the aim of knowing how many factors influence the increase in urbanization in the cities of Jakarta and Surabaya in 2020-2021. The research method is descriptive qualitative method and evaluation. The analytical technique used is library research and also urbanization data in the cities of Surabaya and Jakarta for the period 2020 and 2021 from the Central Statistics Agency. With the results obtained, namely urbanization occurred in the two cities because the income from the two cities was high, namely DKI Jakarta, amounting to Rp. 4,416,186,548 in 2021 while in East Java Province, the highest UMK in 2021 and 2022 is held by the City of Surabaya, which is Rp. 4,300,479 in 2021. The driving factors are economic factors, lack of job opportunities in villages, minimal facilities and infrastructure. infrastructure in the village and the lack of educational facilities and construction and for the pull factor, namely the influence of people who have urbanized to the destination city by beautifying life in the city, it is much better and also easier to get the desired job or also facilitated in opening a business, wages in the city is much higher, more entertainment, tourist attractions or buildings are more and nice to visit and free individuals more freely. The conclusion is that the main factor of urbanization is the economic factor.